Улсын хурал ба эрдэмтэн Дандаа - Лонжид, Зоригт (Historia Mongolarum, 2003)
Converted his citizenship to new independant Mongolia in 1911, Mr. Dandaa was an officer and scholar. He knew several foreign languages and studied Mongolian and World History. He wrote two books. He has been submitting several times proposals to the State Great Khural. In this article I attempt to deal with his role and proposals in the development of the country.